Enhanced Photocatalytic Degradation of Perfluorooctanoic Acid by Mesoporous Sb2O3/TiO2 Heterojunctions - Yao, Xinyun; Zuo, Jiaqi; Wang, Yu-Jue; Song, Ning-Ning; Li, Huang-Hao; Qiu, Kaipei (Frontiers in Chemistry, 2021)
Perfluorooctanoic acid (PFOA), a typical perfluorinated carboxylic acid, is an emerging type of permanent organic pollutants that are regulated by the Stockholm Convention. The degradation of PFOA, however, is quite challenging largely due to the ultra-high stability of C-F bonds. Compared with other techniques, photocatalytic degradation offers the potential advantages of simple operation under mild conditions as well as exceptional decomposition and defluorination efficiency. Titanium dioxide (TiO2) is one of the most frequently used photocatalysts, but so far, the pristine nanosized TiO2 (e.g., the commercial P25) has been considered inefficient for PFOA degradation, since the photo-generated hydroxyl radicals from TiO2 are not able to directly attack C-F bonds. Mesoporous Sb2O3/TiO2 heterojunctions were therefore rationally designed in this work, of which the confined Sb2O3 nanoparticles in mesoporous TiO2 framework could not only tune the band structure and also increase the number of active sites for PFOA degradation. It was found that, after loading Sb2O3, the absorption of UV light was enhanced, indicating a higher efficiency of light utilization; while the band gap was reduced, which accelerated the separation of photo-generated charge carriers; and most importantly, the valence band edge of the Sb2O3/TiO2 heterojunction was significantly lifted so as to prevent the occurrence of hydroxyl radical pathway. Under the optimal ratio of Sb2O3 to TiO2, the resulting catalysts managed to remove 81.7% PFOA in two hours, with a degradation kinetics 4.2 times faster than the commercial P25. Scavenger tests and electron spin resonance spectra further revealed that such improvement was mainly attributed to the formation of superoxide radicals and photo-generated holes, in which the former drove the decarboxylation from C7F15COOH to C7F15•, and the latter promoted the direct electron transfer for the conversion of C7F15COO- to C7F15COO•. The Sb2O3/TiO2 photocatalysts were highly recyclable, with nearly 90% of the initial activity being retained after 5 consecutive cycles, guaranteeing the feasibility of long-term operation.